MOECHTAZAR M PADA MASA PRRI DAN KETERLIBATAN DALAM BIDANG INSTANSI KESEHATAN (INKES) 1956-1960 - -, SARJAN - (Pendidikan Sejarah, 2014)
This study exposes Muchtazar M: his role at PR.RI prior time in Health Foundation (INKES) department 1956 - 1960. Moechta zar M was born on July 30